Hubungan Risiko Tercemar Sumur Gali dengan Keberadaan Bakteri Escherichia Coli di Gampong Daroy Kameu Kecamatan Darul Imarah Kabupaten Aceh Besar Tahun 2017 - Zulfikar Zulfikar; Ratina Putri; Wiwit Aditama (Poltekkes Kemenkes Yogyakarta, 2020)
Wells are one of the means of clean water supplier for rural and urban communities. The risk of bacterial pollution in wells is very large since it is influenced by the lack of concern and know-ledge of the well owners in carrying out maintenance. This study aims to find out the correlation between the pollutionrisk of wells and the presence of Escherichia coli bacteria at Daroy Kameu Village, in Darul Imarah Subdistrict of Aceh Besar District. This study was a descriptive analytic study with a cross sectional design with 30 wells sample. The study was conducted in March to April 2017. The data analysis employed chi-square test, and from the results it can be concluded that there was a correlation between the level of pollution risk of wells and the presence of E. coli bacteria in well water (p = 0,021), a correlation between the distance of dug wells with the pre-sence of E. coli bacteria in well water (p=0,019), a correlation between the walls of well and the presence of E. coli bacteria in well water (p 0.026), a correlation between well’s lip dig and the presence of E. coli bacteria in dug well water (p=0,011), and there was a correlation between the floor of the well and the presence of E. coli bacteria in well water (p=0.030). The community is advised to reduce the level of pollution risk by monitoring and improving the non suitable con-struction of wells, so that the well condition remain safe and can meet the requirements, thus preventing bacterial contamination.